The Challenges Facing Female English Language Teachers in Secondary Schools in Jordan - Khloud Al-Bdeerat; Basil Alqarraleh; Abdel Rahman Mitib Altakhaineh (National Research University Higher School of Economics, 2020)
This study aimed to identify the obstacles facing female secondary teachers of English in Al-Qaser Directorate of Education in Al-Karak, Jordan. For the purpose of the study, a quantitative approach was adopted. The sample was randomly selected and included 170 female English language teachers. A questionnaire consisting of 29 items covering five domains was administered and 150 questionnaires were returned. The results showed that these teachers faced many academic challenges and obstacles in various domains, such as in the student, community, and parent domains, as well as teacher skills, curriculum, and school environment domains. The results also revealed that there were statistically significant differences in the challenges and obstacles faced by the teachers in terms of the experience variable. The study, thus, recommends adopting a more effective strategy to improve the school environment and having a suitable psychological context for female English teachers in order to enhance the quality of the students' learning outcomes.